Characteristics of Drifting Sand Flux over Gobi Surface: A Wind Tunnel Simulation - Zhang, Ke Cum; Zu, Rui Ping; Qu, Jian Jun; Fang, Hai Yad (Annals of Arid Zone, 2016)
Through simulation studies on characteristics of drifting sand flux over Gobi surface in wind tunnel, this paper aims to inquire how the environmental parameters of Gobi surface affect the turbulence of air current, the structure of drifting sand flux and the velocity profile within the boundary layers so that it can provide a theoretical basis for the engineering design of sand-control in Gobi region. The experiment showed that the drifting sand activities mainly focus within 20 cm over the Gobi surface, and there is a good relationship between sand concentration and corresponding wind velocity. However, the distribution pattern of sand concentration takes on a shape like elephant nose over Gobi surface and it does not follow the logarithmic law as it does on sand-bed. This phenomenon mainly results from grain-to-gravel collision over the Gobi surface. By combining the sand concentration with the distribution function of wind velocity, the function of energy distribution within sand-laden layer could be drawn. Key words: Sand-laden layer, structure of sand flux, wind tunnel simulation, wind velocity profile.